Fostering A Multi-level Approach to Entrepreneurial Pedagogy: The German Experience - Magdalena Łuczak-Trąpczyńska; Piotr Trąpczyński (Jesuit University Ignatianum in Krakow, 2017)
RESEARCH OBJECTIVE: The aim of this paper is to analyse the case of entrepreneurial pedagogy in Germany at the level of primary and secondary education and to identify good practices in the development of entrepreneurship skills of pupils. THE RESEARCH PROBLEM AND METHODS: The paper uses a systematic review of literature with relation to entrepreneurial education, as well as the German literature of the topic, in order to descend to the analysis of secondary data related to the German education system and its usage of entrepreneurial pedagogy. THE PROCESS OF ARGUMENTATION: In the first part, the paper clarifies the notion of entrepreneurial pedagogy and introduces modern didactic approaches, particularly process-oriented teaching. Subsequently, the German case is used to analyse how entrepreneurial pedagogy can be implemented at different interrelated levels. In the recommendation section, the success factors of the implementation of such an approach are discussed. The paper ends with some concluding remarks. RESEARCH RESULTS: The analysis of entrepreneurial pedagogy in German literature and practice highlights the relevance of an interplay of solutions at different levels: the level of the state (or, in the case of decentralised educational systems like the German one, at the regional level), the level of school initiative, as well as the individual level of educators who are in charge of implementing entrepreneurial teaching methods. CONCLUSIONS, INNOVATIONS AND RECOMMENDATIONS: According to the concept of process-oriented didactics presented in this paper, the aspect of making mistakes is an important engine of learning, as well as teaching itself. However, it can be observed in Germany that in teaching reality more attention is devoted to the errors themselves than to the tolerance of errors, according to the principle that the teacher does not commit mistakes. Hence, this issue should be raised in appropriate teacher training. The German experience can be a starting point for discussion related to other countries, as well.